2003
DOI: 10.1161/01.str.0000087787.38080.b8
|View full text |Cite
|
Sign up to set email alerts
|

Craniotomy for Treatment of Unruptured Aneurysms Is Not Associated With Long-Term Cognitive Dysfunction

Abstract: Background and Purpose-Many studies have reported frequent cognitive deficits associated with subarachnoid hemorrhage (SAH) and aneurysm repair. One study found more severe cognitive deficits after clipping than coiling of aneurysms, raising the possibility that deficits are due to surgery instead of SAH itself. This possibility was directly addressed by evaluating the cognitive effects of surgery without SAH. The goal of this study was to identify changes in cognitive function associated with surgical clippin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…3 Other previous cognitive study confirmed safe surgery for UIAs, although no CBF study was done. 9 Our results confirmed that neither cognitive function nor CBF decreased after surgery. Previous research showed that surgical repair of UIAs does not affect CBF if the surgery can be completed with fine surgical manipulation.…”
Section: Discussionsupporting
confidence: 78%
“…3 Other previous cognitive study confirmed safe surgery for UIAs, although no CBF study was done. 9 Our results confirmed that neither cognitive function nor CBF decreased after surgery. Previous research showed that surgical repair of UIAs does not affect CBF if the surgery can be completed with fine surgical manipulation.…”
Section: Discussionsupporting
confidence: 78%
“…210,211 There have been contradictory results in series that used more comprehensive neuropsychological batteries. 210,212,213 Nonetheless, it appears that standard outcomes instruments such as the mRS and the Glasgow Outcome Scale do not correlate with results of the Mini-Mental State Examination after aneurysm surgery, 214 and thus, the incorporation of cognitive assessment of patients can provide additional useful outcomes information. A number of small series have also examined quality of life using health outcome scales such as the Short Form-36 and the Hospital Anxiety and Depression Scale (HADS).…”
Section: Surgical Clipping Outcomesmentioning
confidence: 99%
“…Along similar lines, surgical treatment has produced low rates of morbidity and mortality in patients with unruptured aneurysms in expert hands. 5,108,109,123,141 Tuffiash et al 141 demonstrated no cognitive effects of craniotomy for unruptured aneurysms. Furthermore, the unparalleled team of Dr. Charles Drake and colleagues was able to clip unruptured basilar bifurcation aneurysms smaller than 12.5 mm in diameter with a 3.6% risk of poor outcome and no mortality.…”
mentioning
confidence: 99%